Natural Disaster Regionalization and Countermeasures in the Guangdong-Hong Kong-Macao Greater Bay Area Urban Agglomeration - Wang Jun; Wang Xianglin; Gong Qinghua; Yuan Shaoxiong; Liu Bowen (Redai dili)
In the context of global climate change, natural disasters pose increasingly serious threats to the Guangdong-Hong Kong-Macao Greater Bay Area. Therefore, in this study, we aimed to conduct integrated comprehensive zoning of natural disasters and to develop disaster prevention and mitigation countermeasures for the Greater Bay Area. To achieve this objective, we first carried out geomorphological division of the Greater Bay Area based on the land geomorphological classification system. Second, we performed comprehensive zoning of natural disasters according to the intensity of dominant natural disasters in various geomorphological units. Finally, we conducted risk zoning of natural disasters according to the main controlling factors of natural disasters in each zoning units. Based on the geomorphology of the Greater Bay Area and the risk of natural disasters, we proposed natural disaster prevention and mitigation countermeasures. The results show that: (1) The landform of the Greater Bay Area can be divided into four major first-class divisions: mountains, hills, platforms and plains. The landforms of the Greater Bay Area can be divided into 10 secondary subdivisions, including medium-altitude small undulating mountains, low-altitude small undulating mountains, low-altitude erosion and denudation hills, low-altitude erosion and denudation platforms, low-altitude alluvial platforms, low-altitude alluvial flood platforms, low-altitude alluvial plains, low-altitude marine plains, low-altitude marine alluvial plains, and low-altitude estuarine coasts. Among these subdivisions, low-altitude small undulating mountains represent the largest area (21,618.28 km2), while low-altitude erosion and denudation platforms represent the smallest area (849.77 km2). (2) The Greater Bay Area can be divided into three first-level major disaster subdivisions: mountain and hill disaster areas (52.77%), plain and platform disaster areas (40.43%), and estuary and coast disaster areas (6.80%). (3) The Greater Bay Area can be further divided into second-level disaster subdivisions, including the small undulating and low-altitude mountain disaster area, low-altitude alluvial plain land subsidence area, low-altitude plain and platform flood area, and 14 others. The largest second-level disaster subdivision area is the small undulating low-altitude mountain disaster area (20,892.18 km2), which is distributed in the east, north, and west of the Greater Bay Area, followed by the low-altitude plain and platform flood disaster area (13,320.98 km2), which is mainly distributed in Guangzhou, Jiangmen, Shenzhen, Huizhou, and Zhaoqing cities, among other areas. The karst collapse area of the low-altitude platform represents the smallest second-level disaster subdivision (163.62 km2) and is mainly distributed in some areas of Enping and Jiangmen cities. (4) The natural disaster risk in the Greater Bay Area can be divided into high-risk, medium-risk, and low-risk areas. The high-risk areas for mountain disasters are mainly in Deqing, Huaiji, and Guangning of Zhaoqing City; and Conghua District in the north of Guangzhou City, Longmen, Boluo, and other regions in Huizhou City. The high-risk areas for plain and platform disasters are mainly in Doumen District, Zhuhai City, Guanghua Basin, Huadu District, Nansha District, Guangzhou City, Foshan City, and other regions. The high-risk areas for estuary and coast disasters are mainly in Doumen District, Zhuhai City, and near the mouth of the Pearl River Delta. In this study, we proposed disaster prevention and mitigation countermeasures for natural disasters in the Greater Bay Area from four perspectives. Our results serve as a valuable reference for the Greater Bay Area urban agglomeration in regional development planning, comprehensive disaster reduction planning, and the improvement of disaster prevention and mitigation capabilities.